Young researchers’ reflections on workshops with youth to develop research recruitment materials - Zeba Khan; Hajar Seiyad; Kaiya Jacob; Ayla Arhinson; Aleyah Williams; Sarah Munro (Research Involvement and Engagement)
Abstract Background Contraception care is recognized as a basic human right, however, many individuals continue to face challenges in accessing adequate care. For youth, factors that influence access to prescription contraception include affordability, availability, acceptability, and youth awareness of these options. As a result, contraception uptake in Canada remains low, with 22.9% of sexually active 15 to 24-year-olds reporting that they did not use a condom or another form of contraception the last time they had sex. Collaborating with youth and meaningfully engaging them in all stages of the research process may help us better understand and develop solutions and services that yield stronger usability among youth. Main Text We engaged in a co-design process to involve youth in the generation of research recruitment materials. In this article, we offer a rich description of the experiences of youth as embedded researchers and contribute to the methodology of co-design research by highlighting specific characteristics in our approach that facilitated youth engagement. Through a series of six virtual workshops, four youth research assistants and eight youth advisors engaged in discussion activities that generated ideas for the recruitment materials for a research study called ‘Ask Us: Youth Voices to Improve Contraception Access’. Our strategies included the (i) Re-distribution of Power to Enable Youth Participation, (ii) Use of Technology to Promote Collaboration and Confidentiality and (iii) Emphasizing Reciprocal Knowledge Building, to facilitate meaningful youth participation. Conclusions The co-design sessions resulted in the creation of the Ask Us study recruitment materials ( www.askusproject.ca ) and youth informed the chosen wording, colour scheme, images, and more. Our purposeful steps to involve embedded youth research assistants, acknowledge the differences and redistribution of power among researchers and youth advisors, use technology to promote collaboration and confidentiality and emphasize reciprocal knowledge sharing led to a meaningful co-design experience for us as youth research assistants. We argue that deeper considerations of accountability by academic researchers and embedded youth research assistants can further promote youth participation by enabling spaces where youth feel safe.